The schoolwide enrichment model: a comprehensive plan for the development of talents and giftedness - Renzulli, Joseph (Revista Educação Especial, 2014)
http://dx.doi.org/10.5902/1984686X14285 The Schoolwide Enrichment Model (SEM) is widely implemented as an enrichment program used with academically gifted and talented students and a general enrichment approach for all schools interested in developing the strengths and talents of all learners. The major goal of the SEM is the application of gifted education pedagogy to total school enrichment and joyful learning. The SEM provides enriched learning experiences and higher learning standards for all children through three goals: developing talents in all children, providing a broad range of enrichment experiences for all students, and providing advanced level follow-up opportunities for young people based on their strengths and interests. The SEM focuses on enrichment for all students through high levels of engagement and the use of enjoyable and challenging learning experiences that are constructed around students' interests, learning styles, and preferred modes of expression.